The fiscal and intergenerational burdens of brakes and subsidies for energy prices - Johannes Huber; Christian Scharrer (International Tax and Public Finance, 2023)
We study the effects of different financing rules for untargeted energy price brakes and subsidies on intergenerational welfare in a large-scale overlapping generations model. The results indicate that, in comparison with a laissez-faire solution without any government interventions, debt-financed implementations of such measures are very detrimental for young and future generations. However, the taxation of windfall profits can significantly contribute to reduce the economic burdens of these generations; whereas, the positive effects on older generations are much less pronounced.
Keywords: E62; E30; H20; H30; 340; Fiscal policy; Price brakes; Price subsidies; Energy crisis; Welfare